Inclusion of Leguminous Green Manures Enhances Crop Biomass, Nutrient Uptake, Soil Phosphorus Dynamics and Bioavailability - P. V. Nguyen; L. M. Condron; Z. P. Simpson; R. W. McDowell (Journal of Sustainable Agriculture and Environment)
ABSTRACT Introduction In agroecosystems, phosphorus (P) applications over a long time have accumulated in soil as legacy P. This environmental challenge can be an agronomic opportunity as soil legacy P could be recovered in cropping systems using practices such as green manuring. We hypothesised that, at moderate soil available P levels, plant‐soil interactions under green manures can mobilise soil legacy P and promote cereal crop P uptake and growth. Methods Alongside a fallow treatment, three green manure treatments that included two legume treatments (narrow‐leaf lupin [Lupinus angustifolius], pea [Pisum sativum L.]) and one cereal treatment (wheat [Triticum aestivum] and barley [Hordeum vulgare]) were rotated with the main crops of wheat and barley in two phases on a pumice soil (27 mg kg−1 Olsen P) in a microcosm experiment. Plant roots and shoots and end‐of‐experiment soil samples were collected for analysis. Results Over two crop rotations, inclusion of narrow‐leaf lupin and pea green manures significantly increased main crop biomass (27%–35%) and P uptake (15%–29%) relative to control, while the cereal green manure decreased the following crop's yield (−13%) and P uptake (−19%). Relative to fallow, microbial biomass P and soil organic P pools increased under all green manures yet total inorganic P decreased under leguminous green manures. This depletion (35 mg P kg−1) under narrow‐leaf lupin was equivalent to ~47 kg P ha−1. Phosphatase enzyme activities relevant to P cycling increased particularly under leguminous green manure treatments. Conclusions Leguminous green manures such as narrow‐leaf lupin could mobilise soil P to crops in field conditions, suggesting that drawdown of soil legacy P while sustaining crop yield can be tenable.